PENGARUH PRODUK DOMESTIK REGIONAL BRUTO (PDRB), JUMLAH UANG BEREDAR DAN VELOSITAS TERHADAP INFLASI DI RIAU TAHUN 2010-2020 - Damanik Mega Stevenson Julio; Mayes Antony; Richard Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
Inflation is one of the important economic indicators, the rate of change is always tried to be low and stable so that it does not cause macroeconomic diseases which will later have an impact on instability in the economy. High and unstable inflation is a reflection of the tendency of rising prices for goods and services in general and continuously over a certain period of time. The purpose of this study was to analyze the effect of Gross Regional Domestic Product (GRDP), money supply and velocity on inflation in Riau in 2010-2020. This research was conducted in Riau Province, Indonesia by collecting data on the variables of Gross Regional Domestic Product (PRDB), the money supply and velocity and inflation in Riau. This research was conducted in 2021 with a time period of 2010-2020 with this type of research data being secondary data. The data analysis method of this research is descriptive quantitative data analysis using multiple linear regression analysis with data expressed in time series scale. From the results of this study, it can be concluded that the Gross Regional Domestic Product (GRDP) has a positive effect on inflation because from the partial test/t test, the tcount value is greater than ttable. Meanwhile, the amount of money in circulation has no effect on inflation because partially/t-test the value of tcount is smaller than ttable. Finally, velocity has a significant positive effect on inflation because from the partial test/t test, the value of tcount is greater than ttable. The adjusted R square value is 0.879, meaning that 98.7% of the inflation rate in Riau in 2010-2020 can be explained by the variation of the Gross Regional Domestic Product (GRDP)/X1 variable, the money supply/X2 and velocity/X3. While the remaining 1.01% is explained by other variables outside of the research.Keywords : Gross Regional Domestic Product (GRDP), Money Supply, Velosity and Inflation